2016
DOI: 10.1515/znb-2015-0106
|View full text |Cite
|
Sign up to set email alerts
|

Salaterpene E, a eudesmane-type sesquiterpene from Salacia longipes var. camerunensis

Abstract: A mixture of two compounds with potent antiplasmodial activity in vitro against the W2 strain of Plasmodium falciparum (half maximal inhibitory concentration, 1.12 μg/mL) was obtained in a previous investigation of the CH2Cl2-MeOH extract of the seeds of Salacia longipes var. camerunensis. Separation by column chromatography led now to the isolation of salaterpene E (1) and (1R,2R,4S,5S,6R,7R,9S,10R)-2-acetoxy-1,6,9-tribenzoyloxy-4-hydroxy-dihydro-β-agarofuran (2). The structure of 1 was elucidated by spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…The relative stereochemistry has been established from a study of the coupling constants in the 1 H NMR spectrum. Mbaning et al (2016) reported a J value of 7.3 Hz for the axial H9; in our case, H9 has a J value of 7.6 Hz, confirming the stereochemistry of C9 as R. This was later confirmed by the X-ray structure determination. Fig.…”
Section: Nmr Analysissupporting
confidence: 79%
See 1 more Smart Citation
“…The relative stereochemistry has been established from a study of the coupling constants in the 1 H NMR spectrum. Mbaning et al (2016) reported a J value of 7.3 Hz for the axial H9; in our case, H9 has a J value of 7.6 Hz, confirming the stereochemistry of C9 as R. This was later confirmed by the X-ray structure determination. Fig.…”
Section: Nmr Analysissupporting
confidence: 79%
“…Chemical name 1 ALEWOF Mbaning et al (2016) 5-Acetoxy-2-hydroxy-2,6,10,10-tetramethyl-4-oxo-11-oxatricyclo[7.2.1.0 1,6 ]dodecane-7,12-diyl dibenzoate 2 ALEXOG Mbaning et al (2016) 4,5,8-Triacetoxy-2-hydroxy-2,6,10,10-tetramethyl-11-oxatricyclo[7.2.1.0 1,6 ]dodecane-7,12-diyl dibenzoate hexane solvate 3 ALEYOH Mbaning et al (2016) 4-Acetoxy-5,12-bis(benzoyloxy)-2-hydroxy-2,6,10,10-tetramethyl-11-oxatricyclo[7.2.1.0 1,6 ]dodec-7-yl nicotinate 4 CELBRB Smith et al (1976) Celorbicol mono-p-bromobenzoate 5 EJACOI Yeboah et al (2010) 2,6,10,10-Tetramethyl-4-oxo-11-oxatricyclo[7.2.1.0 1,6 ]dodecane-5,7-diyl bis(furan-3-carboxylate) 6 EJACOI01 Yeboah et al 20102,6,10,10-Tetramethyl-4-oxo-11-oxatricyclo[7.2.1.0 1,6 ]dodecane-5,7-diyl bis(furan-3-carboxylate) 7 ISOCEL Smith et al (1976) Isocelorbicol 8 JAGREO Hori et al (1987) Regelidine 9 KUXGEP Tu et al (1990) 1b,2b-Diacetoxy-9a-(3-phenyl-2-oxiranylcarboxy)--dihydroagarofuran 10 KUXGEP10 Wang & Tu (1995) 1b,2b-Diacetoxy-9a-(3-phenyl-2-oxiranylcarboxy)--dihydroagarofuran 11 OSOVUO Torres-Romero et al (2011) 2,6,10,10-Tetramethyl-11-oxatricyclo[7.2.1.0 1,6 ]dodecane-2,5,7,8,12-pentol hemihydrate 12 SIFNEA Begley et al (1990) 6-O-Acetyl-9-O-[(E)-cinnamoyl]-1-O-glycoloyl-1,4,6,9-tetrahydroxydihydroagarofuran 13 UKUBIL Mehta & Kumaran (2003) 7-Benzoyloxy-2,6,10,10-tetramethyl-11-oxatricyclo[7.2.1.0 1,6 ]dodecane-3,4,12-triol 14 UKUBIL01 Kumaran & Mehta (2015) 7-Benzoyloxy-2,6,10,10-tetramethyl-11-oxatricyclo[7.2.1.0 1,6 ]dodecane-3,4,12-triol 15 YABZAC Gonzalez et al (1992) (3S,4R,5R,7R,10R)-3,4-Dihydroxydihydro--agarofuran…”
Section: Number Csd Refcode Referencementioning
confidence: 99%
“…The relative stereochemistry has been established from a study of the coupling constants in the 1 H NMR spectrum. Mbaning et al (2016) reported a J = 7.3 Hz for the axial H9 atom. Compound (III) has a J = 6.6 Hz for atom H9, while compound (IV) has a J = 6.7 Hz for the same correlation, confirming the stereochemistry of C9 (R).…”
Section: Figurementioning
confidence: 99%